Formation of Scientific Knowledge on State Export Control Within the System of Public Administration of National Security - Liakhovych, Halyna; Vakun, Oksana (Public Policy and Accounting, 2024)
Contemporary globalization processes, the growth of military-technical cooperation, and the proliferation of dual-use goods create unprecedented challenges for the system of state management of national security. State export control today is not only an instrument of regulatory policy, but also a key element in preventing the proliferation of weapons of mass destruction, terrorism, and illegal transfers of strategically important technologies. Research into the development of scientific knowledge about state export control allows us to reveal the evolution of scientific approaches, identify conceptual gaps, and propose new models for integrating control mechanisms into national security strategy. The author chose bibliometric analysis, which is an important method of modern research based on the quantitative study of bibliographic data. It allowed identifying trends in the development of scientific publications, assessing their quality, and identifying key changes in certain fields of knowledge. The use of a large data set and statistical methods ensured the objectivity of the results and created a basis for the formation of new scientific knowledge. The results of the bibliometric analysis showed that over the past two decades, scientific research on export control issues has intensified significantly, which is associated with the escalation of hybrid threats, international conflicts, and the growing role of security regulation mechanisms. The systematic increase in publications in Scopus and Web of Science indicates the formation of an interdisciplinary direction that combines economic, political, and legal approaches. Geographical analysis demonstrates the leadership of the United States, the high activity of the EU and East Asian countries, and the development of transatlantic and interregional cooperation. Export control is considered not only in terms of security and non-proliferation of technologies, but also through the prism of global supply chains, economic stability, and innovation.